Analysis of anthocyanins and total flavonoids content in functional rice and its recombination inbred lines - Zhou, Xinyi; Xie, Wei; Jing, Hao; Fu, Junru; Li, Maomao; Bian, Jianmin; Xu, Jie; Cai, Yicong; He, Haohua; Zhou, Dahu (Frontiers in Plant Science, 2023)
With the rise of people's living standards, the market is no longer satisfied with the yield of rice but is more concerned with its quality and nutritional value. In this experiment, we used Zibaoxiangnuo 1 (ZBXN 1), a functional rice variety rich in total flavonoids and anthocyanins, as the experimental material and constructed a recombinant self-incompatible line with Minghui63 (MH63). The results also confirmed that ZBXN 1 is rich and stable in anthocyanins and can be used as an intermediate breeding material for selecting and breeding high-yielding and high-quality varieties rich in anthocyanins. The results also confirmed that ZBXN 1 is rich and stable in anthocyanins and can be used as an intermediate material for breeding and selecting new anthocyanin-rich varieties.